A protective layer for inhibiting the generation of nano-twin copper interface cracks and its preparation method and application

By plating metal protective layer on the nanotwin copper pad and performing low-temperature heat treatment, the alloy coating is formed, which solves the problem of interface cracks caused by sulfate and organic matter during the electroplating process, improves the reliability of the welding joints and is suitable for industrialization Production.

CN115747901BActive Publication Date: 2024-12-27HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211418323.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-14
Publication Date
2024-12-27
Estimated Expiration
2042-11-14

AI Technical Summary

Technical Problem

The sulfates and organic matter doped in the electroplating process of existing nanotwin copper pads lead to the generation of interfacial cracks and vacancy wells, reducing the service reliability of solder joints, and the existing high-temperature annealing treatment method for nanotwin structures Disadvantages, increasing production costs.

Method used

The nanotwin copper plating layer is coated with Mn, Zn, Cr or Ag protective layers, and heat treatment is carried out at 150-250°C to form an alloy coating to suppress the occurrence of interfacial cracks. The nanotwin copper soldering pad is used by DC plating method. A Zn protective layer was plated and heat treatment was performed in an argon atmosphere.

Benefits of technology

It effectively inhibits the diffusion of sulfur elements and vacancy well aggregation, prevents the generation of interface cracks and Kirkendal holes, improves the service reliability of nanotwin copper solder joints, and simplifies the preparation method, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115747901B_ABST
    Figure CN115747901B_ABST
Patent Text Reader

Abstract

The present invention discloses a protective layer for inhibiting the generation of nano-twin copper interface cracks, and a preparation method and application thereof, and belongs to the technical field of electronic packaging and interconnection technology. The present invention solves the problem that when the existing nano-twin copper is used as a soldering pad, there are a large number of vacant wells and sulfur elements inside it, which are continuously enriched during the service process of the solder joint, and finally lead to cracking of the solder joint interface. The present invention uses metal elements to form a coating on the surface of the nano-twin copper plating layer, and cooperates with low-temperature heat treatment to alloy the metal coating, thereby inhibiting the generation of interface cracks on the basis of maintaining the nano-twin structure of the solder pad, and improving the service reliability of the nano-twin copper solder joint. The alloyed coating formed on the surface of the twin copper plating layer of the present invention can significantly inhibit the diffusion of sulfur elements and prevent the aggregation of vacant wells, thereby preventing the generation of interface cracks and the generation of interface Kirkendall holes. In addition, the preparation method of the protective layer provided is simple, suitable for industrial production, and broadens the application of nano-twin copper solder pads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a protective layer for inhibiting the generation of nano-twin copper interface cracks and a preparation method and application thereof, belonging to the technical field of electronic packaging and interconnection technology. Background Art

[0002] In recent years, nano-twinned copper has attracted attention in the field of microelectronics due to its strength and lower resistivity, which is one order of magnitude higher than that of general polycrystalline copper. And because of its nano-level twinned layer structure, the atoms moving through the intersection of twin boundaries and grain boundaries will be hindered for a period of time before continuing to move, thus having strong electromigration resistance, which can hinder the transport of atoms under electromigration, and is very suitable as an interconnect. At this stage, it has been used in microelectronic interconnection as under-bump metallization layer, redistribution line layer and through-silicon via filling material.

[0003] The existing preparation methods of nano-twin copper are mainly magnetron sputtering, rolling and electroplating. In order to improve production efficiency and production accuracy, the current industrial preparation method is mainly direct current electroplating, and its plating solution system is a sulfate system. During the electroplating process, a large current density and stirring rate are applied to promote the formation of the nano-twin layer, but a large amount of sulfate and organic matter are doped in the coating during this process. The doping of sulfate causes the S element to segregate at the Cu / Cu3Sn interface, reducing the interface energy and nucleation barrier, which helps the nucleation of holes at the Cu / Cu3Sn interface. At the same time, the presence of organic impurities hinders the disappearance of diffusion vacancies, so that when the nano-twin copper is used as a pad, there are a large number of vacancy wells inside it, which are continuously enriched during the service process of the solder joint, and finally cause the solder joint interface to crack, greatly reducing the service reliability of the solder joint. Therefore, it is very necessary to provide a technology to inhibit the generation of cracks at the interface of nano-twin copper.

[0004] At present, there are two main methods for dealing with impurities introduced into ordinary pads: first, the electroplated Cu substrate is subjected to a high-temperature annealing treatment at 600°C to eliminate the heterogeneous phase in the coating. However, since nano-twin copper has a nano-level nano-twin layer, its high-temperature stability is poor. It will continue to degrade during the aging process at more than 250°C and no longer have a nano-twin lamellar structure. At the same time, the excessively high treatment temperature causes many voids to appear in the nano-twin copper pad coating. Second, some sulfide-forming elements are added to the solder to inhibit the nucleation of Kirkendall voids. However, since the solder is applied according to the reference standard in the industrial production process, it is impossible to purchase solder with a certain content of a certain element. It can only be customized or smelted by itself, which greatly increases the production cost and seriously limits the industrial application of nano-twin copper pads. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a protective layer for inhibiting the generation of nano-twin copper interface cracks, and a preparation method and application thereof.

[0006] The technical solution of the present invention:

[0007] One of the purposes of the present invention is to provide a method for inhibiting the generation of interfacial cracks in nano-twinned copper, which comprises coating a protective layer of Mn, Zn, Cr or Ag on the nano-twinned copper coating and subjecting the coating to a heat treatment at 150-250°C.

[0008] It is further defined that the thickness of the protective layer is 0.1-10 μm.

[0009] It is further defined that the heat treatment time is 5-200h.

[0010] It is further defined that the heat treatment atmosphere is argon, nitrogen or a mixture of argon and hydrogen.

[0011] It is further defined that the protective layer is plated by electroplating, chemical plating or physical vapor deposition.

[0012] The second purpose of the present invention is to industrially apply the above method of inhibiting the generation of nano-twin copper interface cracks to nano-twin copper pads, specifically, to plate a Zn protective layer on the nano-twin copper pads by direct current electroplating.

[0013] It is further defined that the above application method comprises the following steps:

[0014] S1, preparation of electroplating solution: dissolving zinc chloride, potassium chloride and boric acid in water, and stirring until no solid matter remains to obtain an electroplating solution;

[0015] S2, cathode treatment: the nano-twinned copper pad is ultrasonically cleaned in dilute sulfuric acid, rinsed with deionized water and blown dry;

[0016] S3, electroplating solution activation: pure zinc plate is used as anode, pure copper plate is used as cathode, and DC power is applied for activation;

[0017] S4, coating protective layer: direct current electroplating is performed using pure zinc plate as anode and nano-twinned copper coating as cathode;

[0018] S5, protective layer treatment: rinse the nano-twinned copper pad after electroplating with deionized water and blow dry;

[0019] S6, placing the soldering pad containing the zinc coating in a tube furnace, and performing heat treatment under atmosphere protection to obtain a soldering pad having a copper-zinc alloy layer with a thickness of 1-5 μm on the surface and a nano-twinned copper layer on the rest.

[0020] It is further defined that the plating solution in S1 comprises 50-100 g / L zinc chloride, 150-250 g / L potassium chloride, 20-30 g / L boric acid and the balance water.

[0021] It is further defined that the concentration of dilute sulfuric acid in S2 is 5-20 g / L, and the ultrasonic cleaning time is 5-10 min.

[0022] It is further defined that the DC activation conditions in S3 are: voltage of 2-4V, time of 10-60min.

[0023] It is further defined that the DC electroplating conditions in S4 are: voltage of 2-4V, time of 0.5-10min.

[0024] It is further defined that the heat treatment atmosphere is argon, the temperature is 150-250° C., and the time is 5-200 h.

[0025] The present invention uses metal elements to form a coating on the surface of the nano-twin copper coating, and alloys the metal coating with low-temperature heat treatment, thereby suppressing the generation of interface cracks while maintaining the nano-twin structure of the pad, and greatly improving the service reliability of the nano-twin copper solder joint. Compared with the prior art, it also has the following beneficial effects:

[0026] (1) The alloyed coating formed on the surface of the twinned copper coating of the present invention can significantly inhibit the diffusion of sulfur elements and prevent the aggregation of vacancy wells, thereby preventing the generation of interface cracks and the formation of interface Kirkendall holes.

[0027] (2) The preparation method of the protective layer for inhibiting the generation of nano-twin copper interface cracks provided by the present invention is simple, suitable for industrial production, and broadens the application of nano-twin copper pads. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 The SEM photograph of the cross section of the solder joint obtained by soldering the nano-twinned copper solder pad with a protective layer prepared in Example 1 after the aging test;

[0030] Figure 2 This is a SEM photograph of the cross section of the solder joint obtained by soldering the nano-twinned copper solder pad without a protective layer prepared in Comparative Example 1 after an aging test;

[0031] Figure 3 This is a FIB-SEM photo of the cross section of the protective layer prepared in Example 1;

[0032] Figure 4 This is a curve showing the variation of element content with depth of the nano-twinned copper pad with a protective layer prepared in Example 1;

[0033] Figure 5 This is a curve showing the variation of element content with depth of the nano-twinned copper pad with a protective layer prepared in Example 2;

[0034] Figure 6 The SEM photograph of the cross section of the solder joint obtained by soldering the nano-twinned copper solder pad with a protective layer prepared in Example 2 after the aging test;

[0035] Figure 7 This is a curve showing the variation of element content with depth of the nano-twinned copper pad with a protective layer prepared in Example 3;

[0036] Figure 8 This is a curve showing the variation of element content with depth of the nano-twinned copper pad with a protective layer prepared in Example 4. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0039] In addition, the technical features involved in the different embodiments described below can be combined with each other as long as they do not conflict with each other. The terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0040] Embodiment 1:

[0041] The specific steps of preparing a protective layer on the nano-twinned copper pad in this embodiment are as follows:

[0042] Step A. Preparation of electroplating solution: Dissolve zinc chloride, potassium chloride and boric acid in water, and stir evenly until no solid remains to obtain a plating solution. The plating solution finally contains 70 g / L zinc chloride, 150 g / L potassium chloride, 20 g / L boric acid and the balance water.

[0043] Step B. Cathode treatment: Place the nano-twinned copper pad in dilute sulfuric acid for ultrasonic cleaning, rinse with deionized water and blow dry. The concentration of dilute sulfuric acid is 20 g / L, and the ultrasonic cleaning time is 10 min.

[0044] Step C. Activation of electroplating solution: Use pure zinc plate as anode and pure copper plate as cathode to activate by direct current. The voltage of direct current activation is 4V and the activation time is 20min.

[0045] Step D. Electrogalvanizing: Use the pure zinc plate as the anode and the nano-twinned copper coating as the cathode for direct current electroplating. The direct current electroplating voltage is 4V and the electroplating time is 1 minute.

[0046] Step E: Plating treatment: Rinse the nano-twinned copper pad after electroplating with deionized water and blow dry.

[0047] Step F. Heat treatment: placing the solder pad containing the zinc coating in a tubular furnace, and performing a coating heating treatment under the protection of an argon atmosphere to obtain a heat-treated alloy solder pad, wherein the heat treatment temperature is 200° C. and the heat treatment time is 50 hours.

[0048] The zinc coating obtained in this embodiment is 1 μm. After heat treatment, the surface structure of the zinc coating evolves into a copper-zinc alloy layer, and the rest is a nano-twinned copper layer, such as Figure 3 As shown in Figure 2, the surface element content changes with depth as shown in Figure 2. Figure 4 As shown by Figure 4 It can be seen that the zinc element gradually diffuses into the nano-twinned copper pad during the heat treatment process, and the alloy layer is about 2μm.

[0049] The nano-twinned copper pad with a protective layer obtained in this embodiment was soldered with a solder. The soldering process was 250°C reflow soldering for 2 min. The solder was pure tin. The obtained solder joint was subjected to an aging test. The aging temperature was 200°C and the aging time was 100 h. The solder joint was then cross-sectioned and polished to observe the cross-sectional microstructure. Figure 1 shown.

[0050] Comparative Example 1:

[0051] The difference between this comparative example and Example 1 is that no protective layer is prepared on the nano-twinned copper pad.

[0052] The nano-twinned copper pads were soldered with solder. The soldering process was 250℃ reflow soldering for 2min. The solder was pure tin. The solder joints were subjected to aging test. The aging temperature was 200℃ and the aging time was 100h. The cross-section of the solder joints was then polished and the cross-section morphology was observed. Figure 2 As shown. Figure 2 It can be observed that the holes have been enriched to form cracks, and the solder joints have lost electrical interconnection and mechanical strength. Figure 1 and Figure 2 It can be seen that the protective layer in Example 1 significantly reduces the number of voids in the solder joint cross section of the nano-twin copper pad, and no electrical failure occurs.

[0053] Embodiment 2:

[0054] The difference between this embodiment and embodiment 1 is that the electroplating time in step D is 10 minutes, and the rest of the operation process and parameter settings are the same as those in embodiment 1.

[0055] The specific steps are as follows:

[0056] Step A. Preparation of electroplating solution: Dissolve zinc chloride, potassium chloride and boric acid in water, and stir evenly until no solid remains to obtain a plating solution. The plating solution finally contains 70 g / L zinc chloride, 150 g / L potassium chloride, 20 g / L boric acid and the balance water.

[0057] Step B. Cathode treatment: Place the nano-twinned copper pad in dilute sulfuric acid for ultrasonic cleaning, rinse with deionized water and blow dry. The concentration of dilute sulfuric acid is 20 g / L, and the ultrasonic cleaning time is 10 min.

[0058] Step C. Activation of electroplating solution: Use pure zinc plate as anode and pure copper plate as cathode to activate by direct current. The voltage of direct current activation is 4V and the activation time is 20min.

[0059] Step D. Electrogalvanizing: Use the pure zinc plate as the anode and the nano-twinned copper coating as the cathode to perform direct current electroplating. The direct current electroplating voltage is 4V and the electroplating time is 10 minutes.

[0060] Step E: Plating treatment: Rinse the nano-twinned copper pad after electroplating with deionized water and blow dry.

[0061] Step F. Heat treatment: placing the solder pad containing the zinc coating in a tubular furnace, and performing a coating heating treatment under the protection of an argon atmosphere to obtain a heat-treated alloy solder pad, wherein the heat treatment temperature is 200° C. and the heat treatment time is 50 hours.

[0062] Compared with Example 1, this embodiment increases the electroplating time, and the obtained zinc coating thickness reaches 10 μm. This results in that when the heat treatment time is 50 h, the zinc coating is not completely alloyed, and the surface element content changes with depth as shown in the curve Figure 5 As shown by Figure 5 It can be seen that the zinc element gradually diffuses into the nano-twinned copper pad during the heat treatment process, but is not completely consumed, and the alloy layer is about 10μm.

[0063] The nano-twinned copper pad with a protective layer obtained in this embodiment was soldered, the soldering process was 250°C reflow soldering for 2 min, the solder was pure tin, and the obtained solder joint was subjected to an aging test, the aging temperature was 200°C, the aging time was 100 h, and then the cross-section of the solder joint was polished and the cross-section microstructure was observed, such as Figure 6 As shown, compared Figure 1 , Figure 2 and Figure 6 It can be seen that the nano-twinned copper pad with a protective layer obtained in this embodiment still has good performance.

[0064] Embodiment 3:

[0065] The difference between this embodiment and embodiment 1 is that a protective layer is prepared on the nano-twinned copper pad by chemical plating, and the specific operation steps are as follows:

[0066] Step A. Preparation of chemical plating solution: Dissolve citric acid, zinc sulfate and sodium hypophosphite in water, stir evenly until no solid remains to obtain a plating solution, and use sodium hydroxide to adjust the pH value of the solution to 4. The plating solution finally contains 10 g / L citric acid, 60 g / L zinc sulfate, 70 g / L sodium hypophosphite and the balance water.

[0067] Step B. Pretreatment: Place the nano-twinned copper pad in dilute sulfuric acid for ultrasonic cleaning, rinse with deionized water and blow dry. The concentration of dilute sulfuric acid is 20 g / L, and the ultrasonic cleaning time is 10 minutes.

[0068] Step C. Chemical zinc plating: Place the nano-twinned copper coating in a plating solution and perform chemical plating at 80° C. for 30 seconds.

[0069] Step E: Plating treatment: Rinse the nano-twinned copper pad after electroplating with deionized water and blow dry.

[0070] Step F. Heat treatment: placing the solder pad containing the zinc coating in a tubular furnace, and performing a coating heating treatment under the protection of an argon atmosphere to obtain a heat-treated alloy solder pad, wherein the heat treatment temperature is 200° C. and the heat treatment time is 50 hours.

[0071] The zinc coating obtained in this embodiment is 2 μm. The curve of the surface element content of the zinc coating after heat treatment with depth is as follows: Figure 7 As shown by Figure 7 It can be seen that the chemically galvanized element layer can also gradually diffuse into the nano-twinned copper pad during the heat treatment process, and the alloy layer is about 3μm.

[0072] Embodiment 4:

[0073] The difference between this embodiment and embodiment 1 is that the heat treatment temperature in step F is 200° C. and the duration is 100 h. The rest of the operation process and parameter settings are the same as those in embodiment 1.

[0074] The specific steps are as follows:

[0075] Step A. Preparation of electroplating solution: Dissolve zinc chloride, potassium chloride and boric acid in water, and stir evenly until no solid remains to obtain a plating solution. The plating solution finally contains 70 g / L zinc chloride, 150 g / L potassium chloride, 20 g / L boric acid and the balance water.

[0076] Step B. Cathode treatment: Place the nano-twinned copper pad in dilute sulfuric acid for ultrasonic cleaning, rinse with deionized water and blow dry. The concentration of dilute sulfuric acid is 20 g / L, and the ultrasonic cleaning time is 10 min.

[0077] Step C. Activation of electroplating solution: Use pure zinc plate as anode and pure copper plate as cathode to activate by direct current. The voltage of direct current activation is 4V and the activation time is 20min.

[0078] Step D. Electrogalvanizing: Use the pure zinc plate as the anode and the nano-twinned copper coating as the cathode for direct current electroplating. The direct current electroplating voltage is 4V and the electroplating time is 1 minute.

[0079] Step E: Plating treatment: Rinse the nano-twinned copper pad after electroplating with deionized water and blow dry.

[0080] Step F. Heat treatment: placing the solder pad containing the zinc coating in a tube furnace, and performing coating heating treatment under the protection of an argon atmosphere to obtain a heat-treated alloy solder pad, wherein the heat treatment temperature is 200° C. and the heat treatment time is 100 h.

[0081] The curve of surface element content of zinc coating after heat treatment with depth is as follows Figure 8 As shown by Figure 8 It can be seen that the zinc element gradually diffuses into the nano-twinned copper pad during the heat treatment process. Compared with the alloy layer obtained in Example 1, the alloy layer diffuses farther and is more evenly distributed. The alloy layer is about 6 μm.

[0082] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. An application of a method for inhibiting the generation of nano-twinned copper interface cracks, characterized in that: A Zn protective layer is plated on the nano-twinned copper pad by direct current electroplating, which specifically includes the following steps: S1, preparation of electroplating solution: dissolving zinc chloride, potassium chloride and boric acid in water, and stirring until no solid matter remains to obtain an electroplating solution; S2, cathode treatment: placing the nano-twinned copper pad in dilute sulfuric acid for ultrasonic cleaning, rinsing with deionized water and drying, wherein the concentration of the dilute sulfuric acid is 5-20 g / L, and the ultrasonic cleaning time is 5-10 min; S3, electroplating solution activation: pure zinc plate is used as anode, pure copper plate is used as cathode, and DC power is applied for activation; S4, coating protective layer: direct current electroplating is performed using pure zinc plate as anode and nano-twinned copper coating as cathode; S5, protective layer treatment: rinse the nano-twinned copper pad after electroplating with deionized water and blow dry; S6, placing the soldering pad with the zinc coating in a tube furnace, and performing heat treatment under atmosphere protection to obtain a soldering pad with a copper-zinc alloy layer with a thickness of 0.1-10 μm on the surface and a nano-twinned copper layer on the rest; The heat treatment atmosphere is argon, the temperature is 150-250°C, and the time is 5-200h.

2. The method for inhibiting the generation of nano-twinned copper interface cracks according to claim 1, characterized in that: The plating solution contains 50-100 g / L zinc chloride, 150-250 g / L potassium chloride, 20-30 g / L boric acid and the balance water.

3. The method for inhibiting the generation of nano-twinned copper interface cracks according to claim 1, characterized in that: The DC activation voltage is 2-4V and the time is 10-60min; the DC plating voltage is 2-4V and the time is 0.5-10min.